Collaborative governance or state regulation? Endless efforts but little capacity for sustainability transformation of the German textile sector. (7th June 2022) - Beyers, Felix; Leventon, Julia; Heinrichs, Harald
Abstract: Collaborative governance is increasingly demanded in multiple sectors and considered promising to address wicked sustainability challenges. Whether it meets these expectations remains uncertain, particularly as such initiatives take place within a broader landscape of public and private policies and projects. We explore how collaborative governance initiative is shaped by its broader landscape to deliver on its goals. To do so, we provide a framework for analysing governance modes and social interactions in collaborative governance. We use an exploratory case study of the German Partnership for Sustainable Textiles (hereafter: Textiles Partnership). The partnership is a multi‐stakeholder, collaborative governance initiative that links to a variety of different initiatives, and highlights barriers and transformation potential both within and outside its boundaries. Based on qualitative interviews, analysis of policy documents and a focus group discussion, we show that the complexity of the landscape field is accompanied by capacity constraints for all actors involved. Such complexity raises questions about whether this governance mode influences actual change on the ground, or diverts energies into navigating and proliferating complexity with low levels of meaningful outcomes. There is a growing call from actors within the partnership towards more state‐centred regulation, resulting in a Due Diligence Act in 2021, to regulate corporate action across national borders. The evidence we present shows the need to reconsider the balance between state regulation and collaborative governance arrangements.